The effects of perioperative dexmedetomidine infusion on hemodynamic stability during laparoscopic adrenalectomy for pheochromocytoma: a randomized study - Kim, Youngwon; Yoo, Young Chul; Kim, Na Young; Shin, Hye Jung; Kweon, Ki Hong; Moon, Jiae; Kang, Sang-Wook (Frontiers in Medicine, 2023)
Introduction Pheochromocytoma is a rare catecholamine-producing neuroendocrine tumor originating from the adrenal medulla chromaffin cells. Hemodynamic instability can occur during the induction of anesthesia and surgical manipulation of the tumor. This study investigated the effects of intraoperative dexmedetomidine administration on hemodynamic stability in patients undergoing laparoscopic adrenalectomy for pheochromocytoma. Methods Forty patients who underwent laparoscopic adrenalectomy for pheochromocytoma were randomly assigned to the dexmedetomidine (n = 20) or control (n = 20) group. The primary outcome of this study was intraoperative hemodynamic stability, and the secondary endpoint was the plasma catecholamine concentrations, specifically of epinephrine and norepinephrine. Results The intraoperative maximum blood pressures were significantly lower in the dexmedetomidine group (control vs. dexmedetomidine group: 182 ± 31 vs. 161 ± 20, 102 ± 17 vs. 90 ± 10, and 128 ± 22 vs. 116 ± 12 [mean ± SD] mmHg and p = 0.020, 0.015, and 0.040 for systolic, diastolic, and mean blood pressure, respectively). The maximum heart rate during surgery was 108 ± 15 bpm in the control group and 95 ± 12 bpm in the dexmedetomidine group (p = 0.010). Other parameters of hemodynamic instability were comparable between both groups. Plasma catecholamine concentrations did not differ between the groups. Conclusion Dexmedetomidine infusion following the induction of anesthesia at a rate of 0.5 μg/kg/h significantly attenuated the maximum intraoperative SBP, DBP, MBP, and HR, contributing to improved hemodynamic stability.